Synthesis of Biogenic High-Magnesium Calcite and its Experimental Immobilization Effect on Cd2+. Issue 6 (1st June 2021) - Wang, Xingxing; Zhu, Xue; Zhang, Luting; Yu, Chengfeng; Lian, Bin
Abstract: Biogenic carbonates usually differ significantly both in physical and chemical characteristics from those of the same chemical origin, and heavy metal immobilization is prominent among these differences. In this research, a biosynthetic method of high-magnesium calcite (HMC) generated by Bacillus velezensis ( B. velezensis ) in the presence of humic acid (HA) was developed to ascertain the immobilization characteristics of biogenic high-magnesium calcite (BHM) for Cd 2+ . The study showed that the presence of HA was crucial to the formation of crystalline BHM. The Cd 2+ immobilization assay results indicated that significant amounts of Cd 2+ could be adsorbed and the obtained data could fit the Langmuir equation ( R 2 = 0.98, Q max = 65.36 mg/g), and the adsorption process conformed to the pseudo-second order kinetic model ( R 2 = 0.99). In particular, BHM can maintain the adsorption capacity at above 100 mg/g even under acidic conditions (pH ≥ 3). Further analysis showed that the adsorption was mainly monolayer physical adsorption, and a small amount of chemisorption also occurred. Thermodynamic parameters (Δ G  > 0, Δ H  > 0, and Δ S  < 0) indicated that the adsorption process was a non-spontaneous endothermic reaction. XRD and SEM-EDS analyses demonstrated that the culture precipitate obtained was mainly HMC, with numerous 10-nm pores based on Barrett-Joyner-Halenda theory of surface area. The results of TG-DTG/DTA analysis showed that the BHM contained about 31.31 ± 3.77% organic matter. Amorphous CdCO3 and the complex or chelate bearing Cd 2+ formed in adsorption process could ensure low desorption, implying a novel prospect for remediation of heavy metal pollution using BHM.